2007
DOI: 10.1016/j.drugalcdep.2007.06.008
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of cumulative and proximal adversity to onset of substance dependence symptoms in two American Indian communities

Abstract: The proximal and distal effects of adversity on the onset of symptoms of substance dependence during adolescence were explored in two culturally distinct American Indian (AI) reservation communities (Northern Plains and Southwest). Data (N=3,084) were from the American Indian Service Utilization, Psychiatric Epidemiology, Risk and Protective Factors Project (AI-SUPERPFP). The age-related risk of symptom onset increased gradually from age 11 through age 16, remained relatively high through age 18, then declined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 35 publications
0
35
0
Order By: Relevance
“…For example, one study reported an increase of approximately 6% in alcohol use from 7 th grade to 12 th grade (Blum et al, 1992) while another study linked early marijuana use (i.e., 11–12 years) to greater odds of marijuana abuse/dependence in late adolescence (Cheadle and Sittner Hartshorn, 2012). Several other studies have shown that substance use begins early among AI adolescents, and early use is a clear marker of risk for prolonged and problematic use (Novins and Baron, 2004; Whitbeck et al, 2008; Whitesell et al, 2007). Together these findings suggest early intervention/prevention is key to eliminating and reducing these observed substance use disparities.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study reported an increase of approximately 6% in alcohol use from 7 th grade to 12 th grade (Blum et al, 1992) while another study linked early marijuana use (i.e., 11–12 years) to greater odds of marijuana abuse/dependence in late adolescence (Cheadle and Sittner Hartshorn, 2012). Several other studies have shown that substance use begins early among AI adolescents, and early use is a clear marker of risk for prolonged and problematic use (Novins and Baron, 2004; Whitbeck et al, 2008; Whitesell et al, 2007). Together these findings suggest early intervention/prevention is key to eliminating and reducing these observed substance use disparities.…”
Section: Discussionmentioning
confidence: 99%
“…evidence of clear links between adversity and suD in other populations (Dawson et al, 2005;Dohrenwend, 2000;Kessler et al, 1997;lloyd, 1995, 2003) has led to speculation that the harsh and often violent conditions on some reservations may be one root cause of substance-use disparities. a growing body of research on the association of adversity with substance-use problems among american indians supports this possibility, but many questions remain (hawkins et al, 2004;Koss et al, 2003;libby et al, 2004;Robin et al, 1999;Rodgers and Fleming, 2003;Walters et al, 2002;Whitesell et al, 2007a).…”
Section: Exposure To Adversity and Risk For Substance-use Disordermentioning
confidence: 99%
“…on the other hand, once substance use has begun, misuse of substances can make individuals more prone to put themselves in risky situations (e.g., driving while intoxicated and fighting) and encounter adversity (e.g., automobile accidents, physical assault) (hingson et al, 2008; spooner, 1999; turner and lloyd, 2003). empirical evidence supports the role of stressors in the initiation and early development of substance use (leMaster et al, 2002;Whitesell et al, 2007a). Yet most agree that once use is initiated, the developmental progression is characterized by a cyclical interplay of stress and increasing substance use (aneshensel, 1999; brennan et al, 1999; stewart and conrod, 2002), both because use increases subsequent exposure to stressful events and because it may interfere with adaptive responses to such events (chilcoat and Menard, 2003).…”
Section: Exposure To Adversity and Risk For Substance-use Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…No other individual-level predictor was found to be a significant predictor across each of the four models. This is not a novel finding, since other studies have also found that such stressors (LeMaster, Connell, Mitchell, & Manson, 2002; Whitesell, Beals, Mitchell, Keane, Spicer, & Turner, 2007; Cheadle & Whitbeck, 2011) and exposure to delinquent peers (Cheadle & Whitbeck, 2011) are predictive of AI substance use, but it does promote further confidence in the generalizability of such predictors of substance use across racial and ethnic groups.…”
Section: Discussionmentioning
confidence: 61%